PUBLIC FINANCE AND ECONOMIC GROWTH IN NIGERIA - Adeoye Afolabi (Malete Journal of Accounting and Finance)
The paper evaluated the public finance in the military and civilian regime. It also examined the effects of recurrent expenditure, capital expenditure and revenue on Gross Domestic Product (GDP). The methodology used for this paper was mixed method. ARDL (Auto-Regression Distributed Lag) bounds test approach was used to estimate the result of this study. The finding of the study revealed that recurrent expenditure was more prevalent under civilian governments than the military governments. The ARDL (Auto-Regression Distributed Lag) indicated that revenue is significant in reducing the Gross Domestic Product. This finding suggests what is currently happening with the Federal Government where revenue adversely affect the Gross Domestic Product. The study recommends that the Federal Government should find more sources of revenue and the government spending should pass through proper accountability and transparent process.